Defending Iot from Ddos Using Lightweight Authentication - A. Vani, G.; Metilda Florence, M. (International Journal of Engineering and Technology, 2018)
The emergence of Internet of things (IoT) is due to itsÂ Â ability to dutifully transfer the data through a network. Now the concern is that security is not considered as main priority while developing the product. IoT is prone to vulnerabilities where Botnet and DDoS kind of attacks are common and a major issue that has to be considered these days. Since IoT is in no way resistive to attacks, this paper is all about proposing a solution for the Distributed Denial of Services attack that happens on IoT platform. Light weight authentication is necessary for any IoT devices because to reduce the power consumption and increase the processing speed of the device [16]. The experimental setup is built on OS named Contiki with cooja simulator that suits to all the devices that are in the IoT environment.Â Â Â